REKOMENDASI PENJUALAN AKSESORIS HANDPHONE MENGGUNAKAN METODE ANALITYCAL HIERARCHY PROCESS (AHP) - Widyasuti, Meilin; Wanto, Anjar; Hartama, Dedy; Purwanto, Eko (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2017)
Talk about the lifestyle that is now growing, it also affects the appearance of mobile phones that are owned by everyone that is more complete mobile accessories and create attractive appearance. Along with the time mobile phone accessories business is also experiencing a fairly rapid development, not even just a store product that sells mobile phone accessories but also has sold the counter. Here the researchers want to examine the recommendation of mobile accessories, where the selected accessories are the accessories of the most popular consumers based on store ratings. The rise of accessories business is proving that the mobile phone accessories still deserve to be a good opportunity. Some telemonication experts predict that mobile users are increasing the number of populations. This can be an accessory business that has good prospects in the future. Based on the results of research using AHP method with 6 samples of best selling mobile accessories, where the data obtained based on the results of interviews with mobile shops in the city Pematangsiantar, obtained the calculation of AHP method for handpone accessories recommendation is 1. Led Selfie (34%), 2. Gopro (25%), 3. Phone Ring (20%), 4. Scean Guard (16%), 5. Charge Wireless (14%) and 6. Handset (10%)